2004
DOI: 10.1002/jmri.20148
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of T with fixed charge density in cartilage

Abstract: Purpose:To establish the specificity of T 1 with respect to fixed charge density (FCD) as a measure of proteoglycan (PG) content in cartilage during the onset of osteoarthritis (OA). Materials and Methods:T 1 -weighted and sodium MRI were performed on cartilage samples of enzymatically degraded bovine explants and natural osteoarthritic human samples representing controlled and physiological models of OA, respectively. Spatial maps of T 1 and FCD (measured using the previously validated method of sodium MRI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
127
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 28 publications
3
127
1
1
Order By: Relevance
“…This is completely in conflict with several results from IL-1b studies on a larger group of samples and on an in vivo animal model where a significant increases in T 1r ( Figure 25) were observed (54,177). (3) At the higher field (8.5 T), T 1r should be lower than that at 1.5 T, but the T 1r numbers measured in human cartilage in this study are almost 50% higher than those observed at 1.5 T. This result was not explained.…”
Section: Experimental T 1r Studiescontrasting
confidence: 72%
See 3 more Smart Citations
“…This is completely in conflict with several results from IL-1b studies on a larger group of samples and on an in vivo animal model where a significant increases in T 1r ( Figure 25) were observed (54,177). (3) At the higher field (8.5 T), T 1r should be lower than that at 1.5 T, but the T 1r numbers measured in human cartilage in this study are almost 50% higher than those observed at 1.5 T. This result was not explained.…”
Section: Experimental T 1r Studiescontrasting
confidence: 72%
“…In direct contradiction to the above study, in human OA specimens (n ¼ 7) with different Mankin grades (0-3), a strong correlation between T 1r rate and FCD measured from sodium MRI was observed (Figure 28), indicating that T 1r relaxation rate may be useful in studying the OA process in humans (177). Nevertheless, a study on a large group of human osteoarthritic specimens is needed to obtain statistically significant results.…”
Section: Experimental T 1r Studiesmentioning
confidence: 71%
See 2 more Smart Citations
“…In contrast to previous studies (19,20), in the current study we aimed to measure T 1 relaxation in human cartilage specimens obtained from surgical replacement of knee joints. Recent in vitro and in vivo studies on cartilage have demonstrated that the T 1 is sensitive to changes in the PG content of cartilage (7,8,21). In a study of bovine cartilage it was shown that the T 1 relaxation rate changes linearly with changes in the PG content of cartilage (6).…”
mentioning
confidence: 99%